The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1016/0041-008x(86)90317-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and brain neurotoxic esterase: Dose and time dependence of inhibition in the hen examined with three organophosphorus esters

Abstract: Certain organic phosphorus esters produce sensorimotor axonopathy in man and other species. There is an excellent correlation between the capacity of an organophosphorus compound to produce axonopathy and its ability to inhibit brain neurotoxic esterase (NTE) in hens. Because NTE is present in peripheral lymphocytes of both hen and man, it has been suggested that the lymphocyte enzyme might be useful both in experimental and clinical situations as an indicator of exposure to organophosphorus compounds producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Inhibition of brain NTE within hours of exposure to a neuropathic OP compound predicts the potential for OPIDN to appear in susceptible animal models (e.g., adult hens) after a delay of 1 to 3 wk. NTE has also been found in circulating lymphocytes and platelets (Bertoncin etal., 1985;Dudek & Richardson, 1982;Maroni & Bleecker, 1986;Richardson & Dudek, 1983), and lymphocyte NTE has been used or proposed for use as an accessible biomarker of animal and human exposure to neuropathic OP compounds (Johnson, 1990;Lotti, 1986;Lotti et al, 1983Lotti et al, , 1986Richardson & Dudek, 1983;Schwab & Richardson, 1986). Furthermore, lymphocyte NTE inhibition has been suggested as a predictor of OPIDN or an adjunct for its early diagnosis (Ehrich, 1996;Lotti, 1987;Mutch et al, 1992;Richardson & Dudek, 1983;Wilson & Henderson, 1992).…”
Section: And Between Brain and Blood (R = 997) The Results Suggest mentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of brain NTE within hours of exposure to a neuropathic OP compound predicts the potential for OPIDN to appear in susceptible animal models (e.g., adult hens) after a delay of 1 to 3 wk. NTE has also been found in circulating lymphocytes and platelets (Bertoncin etal., 1985;Dudek & Richardson, 1982;Maroni & Bleecker, 1986;Richardson & Dudek, 1983), and lymphocyte NTE has been used or proposed for use as an accessible biomarker of animal and human exposure to neuropathic OP compounds (Johnson, 1990;Lotti, 1986;Lotti et al, 1983Lotti et al, , 1986Richardson & Dudek, 1983;Schwab & Richardson, 1986). Furthermore, lymphocyte NTE inhibition has been suggested as a predictor of OPIDN or an adjunct for its early diagnosis (Ehrich, 1996;Lotti, 1987;Mutch et al, 1992;Richardson & Dudek, 1983;Wilson & Henderson, 1992).…”
Section: And Between Brain and Blood (R = 997) The Results Suggest mentioning
confidence: 99%
“…Assay of lymphocyte NTE was shown to provide a reliable monitor of exposure to neuropathic OP compounds within 24h between exposure and measurement (Schwab & Richardson, 1986). To study the possibility of using blood NTE inhibition as a biochemical marker of neuropathic OP exposure and its correlation with brain NTE inhibition, two dosing experiments were carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have been used to test correlations of inhibition in lymphocytes with that in brain (Makhaeva et al, 2003(Makhaeva et al, , 2007Richardson and Dudek, 1983;Richardson et al, 1993a,b;Schwab and Richardson, 1986). Lymphocyte NTE activity has been characterized in human populations (Bertoncin et al, 1985;Maroni and Bleecker, 1986) and used to monitor occupational exposures to potentially neuropathic OP compounds (Lotti et al, 1983(Lotti et al, , 1986McConnell et al, 1999).…”
Section: Biomarkers and Biosensorsmentioning
confidence: 99%
“…A more detailed time-course study indicated a strong correlation between the levels of muscarinic receptors in brain areas and lymphocytes during the period of exposure (65 (81,82). Within 24 hr after acute exposure, there is a good correlation between lymphocyte and brain NTE in the hen, which is the species of choice for OPIDP studies (83). Measurement of lymphocyte NTE has been suggested as a potential biomarker to monitor for organophosphate-induced polyneuropathy (84).…”
Section: Organophosphorus Insecticidesmentioning
confidence: 99%